Systematic meta‐analysis of the risk factors for deliberate self‐harm before and after treatment for first‐episode psychosis. (9th January 2013) - Challis, S.; Nielssen, O.; Harris, A.; Large, M.
Abstract : Objective: Attempted suicide and deliberate self‐injury can occur before or after presentation with a first‐episode of psychosis. The aim of the study is to identify the factors associated with suicide attempts or deliberate self‐injury before and after treatment for first‐episode psychosis. Method: A systematic review and meta‐analysis of controlled studies of factors associated with either suicide attempts or deliberate self‐injury, referred to here as deliberate self‐harm (DSH). Results: The pooled proportion of patients who reported DSH prior to treatment for first‐episode psychosis was 18.4% (95% Confidence Interval (CI) 14.4–23.3, N  = 18 studies, I 2  = 93.8). The pooled proportion of patients with DSH during the period of untreated psychosis was 9.8%, (95% CI 6.7–14.2, N  = 5 studies, I 2   = 58.9). The pooled proportion of patients committing DSH during periods of follow up of between 1 and 7 years was 11.4%, (95% CI, 8.3–15.5, N  = 13 studies, I 2   = 89.2). Categorical factors associated with an increased risk of DSH were a prior history of DSH (OR   = 3.94), expressed suicide ideation (OR   = 2.34), greater insight (OR   = 1.64), alcohol abuse (OR   = 1.68) and substance use (OR   = 1.46). Continuous variables associated with an increased risk of DSH were younger age of onset (Standardized Mean Difference (SMD)   = −0.28), younger age at first treatment (SMD = −0.18), depressed mood (SMD   = 0.49) and the duration of untreated psychosis (SMD   = 0.20). Depressed mood and substance use were associated with DSH both before and after treatment, negative symptoms were associated with DSH after treatment but not before treatment. Positive symptoms and social and global functioning were not associated with DSH. Younger age and the duration of untreated psychosis were associated with DSH before treatment but not after treatment. Conclusion: Earlier treatment of first‐episode psychosis and successful treatment of depression and substance use could prevent some episodes of DSH and might reduce suicide mortality in early psychosis.